In situ transformation from P phase to μ phase in rhenium-containing single-crystal superalloy during thermal exposure. (4th May 2017) - Gao, Shuang; Liu, Zhi-Quan; Cui, Jingping; Zhou, Yizhou; Jin, Tao
Abstract: An in situ phase transformation from P to μ in a rhenium-containing superalloy during high-temperature exposure has been investigated by transmission electron microscopy. The orientation relationship between the phases is found as (1–12)μ // (1 0 0)P and [2 4 1]μ // [0 1 1]P . An atomic model of the μ/P interface was built to reveal a perfectly coherent interface with lattice misfits of only 0.421 and 1.098%. Considering the small lattice distortions and the similar elemental composition of the phases, it is concluded that the phase transformation from P to μ is favourable.